Synthesis of AlN single crystal by solution growth method using type 430 ferritic stainless steel flux - Sen Li; Masayoshi Adachi; Makoto Ohtsuka; Hiroyuki Fukuyama (AIP Advances, 2023)
We propose a new AlN crystal growth method using Fe-based fluxes. AlN single crystals with a thickness of 67–212 µm were epitaxially grown on an AlN bulk substrate by a solution growth method using type 430 ferritic stainless steel flux. The full width at half maximum values of the x-ray rocking curves of (0002) and (10–12) of the synthesized AlN were 137 and 83 arcsec, respectively. The impurity concentrations of carbon were significantly decreased from 3 × 1019 atoms/cm3 in seed crystal to 6 × 1017 atoms/cm3 in synthesized crystal. The features of the method developed in this study are described as follows: (1) steel-based alloys are used as a flux, which are readily available and low-cost; (2) the growth temperature is 1700 °C, which is much lower than that of the sublimation method; (3) no high-pressure vessel is required because growth can be performed under 1 atmospheric pressure conditions; and (4) waste gas detoxification equipment is not required because only N2 gas is used and no toxic or flammable gases are used. Because of the above features (1) through (4), this is an effective crystal growth process from the perspective of ensuring the economics and safety of the facility.